Münsteraner Ernährungsmuster- und Lebensstilstudie bei Schulkindern: MEALS 2006 - Konstantin von Normann (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2007)
A school study of food pattern and life styles of more than 900 pre-college pupils aged 10 to 16 years in Münster, Germany shows that the participants, according to the recommendations of the Dortmund Research Institute of Child Nutrition, nourish themselves in no more than a marginally acceptable manner. The everyday consumption of fruit as well as of meat, meat products and potatoes several times a week is favourable. Conversely, the low consumption of fish, vegetables, wholemeal bread and milk products, as well as the high consumption of sweets, is unfavourable. These results largely confirm other, especially representative, German studies. Every second child establishes its life style long before its 13th birthday. The four empirically-identified life styles can be separated by the food patterns. Family-centred children have comparatively favourable consumption patterns, outdoor & sociable youth and sport & leisure/culture-oriented youth have acceptable food patterns, while multimedia kids prefer unhealthy food and refuse healthy food more than other children. Furthermore a link is evident between life style and individual perceptions of self-sufficiency. The connection is positive for outdoor & sociable youth and sport & leisure/culture-oriented youth who perceive themselves as exceptionally self-sufficient. Family-centred children and multimedia kids often perceive themselves as less self-sufficient. This seems more problematic with multimedia kids, because they also have the most unhealthy food patterns. The results confirm the fact that explicit consumption-related and food-related education should commence not only when the children are about 12 years old, but take place in all classes and school forms and in the form of a separate and distinct subject.
Keywords: A21; D12; I21; J13; 330; Ernährungsgewohnheit; Schüler; Lifestyle; Deutschland